KEPEMIMPINAN TRANSFORMATIF DALAM LEMBAGA PENDIDIKAN ISLAM - Bustari, Bustari; Arif, Muhammad; Yunita, Nurma; Sari, Novira Chintya (UIN Imam Bonjol Padang, 2020)
In this era of globalization, it is necessary to have a leader who is able to manage his subordinates and institutions well. Leadership like this is very much needed in improving the quality of an institution so that it can survive. This study aims to determine the transformative leadership model in Islamic educational institutions. This research uses qualitative methods with the type of literature study. Data collection techniques are obtained from various sources, both journals, books and relevant documents. The results of this study indicate that transformative leadership has a positive impact on an Islamic educational institution, where transformative leadership can improve the performance of Human Resources (HR) for Islamic educational institutions. With the existence of transformative leadership in an educational institution, it can assist the institution in developing its organization. In addition, this leadership can motivate other leaders in leading an organization, both an Islamic educational institution and educational institutions in general.